Greenhouse gas emissions and carbon footprint of collard greens, spinach and chicory production systems in Southeast of Brazil - Pereira, Breno de Jesus; Cecílio Filho, Arthur Bernardes; La Scala, Newton; Figueiredo, Eduardo Barretto de (Frontiers in Plant Science, 2022)
Food production in sustainable agricultural systems is one of the main challenges of modern agriculture. Vegetable intercropping may be a strategy to mitigate greenhouse gas (GHG) emissions, replacing monoculture systems. The objective is to identify the main emissions sources and to estimate GHG emissions of intercropping and monoculture production of collard greens, New Zealand spinach and chicory. Four scenarios were evaluated: ICS – intercropping collard greens and spinach; MCS – monoculture collard greens and spinach; ICC – intercropping collard greens and chicory; MCC - monoculture collard greens and chicory. The boundaries’ reach from “cradle-to-gate” and the calculation of GHG emissions were performed using IPCC methodology and specific factors (Tier 2). The total GHG emitted was standardized as CO2 equivalent (CO2eq). The GHG emissions in ICS and ICC scenarios were approximately 31% lower than in MCS and MCC scenarios. Carbon footprint in ICS (0.030 kg CO2eq kg-1 vegetables year-1) and ICC (0.033 kg CO2eq kg-1 vegetables year-1) scenarios were also lower than in MCS (0.082 kg CO2eq kg-1 vegetables year-1) and MCC (0.071 kg CO2eq kg-1 vegetables year-1) scenarios. Fertilizers, fuel (diesel) and irrigation were the main contributing sources for total GHG emitted and carbon footprint in all evaluated scenarios. The results suggest that intercropping systems may reduce GHG emissions associated with the production of vegetables evaluated as compared with monoculture.